2015
DOI: 10.1007/s00726-015-2042-x
|View full text |Cite
|
Sign up to set email alerts
|

Composition of distinct sub-proteomes in Myxococcus xanthus: metabolic cost and amino acid availability

Abstract: Subsets of proteins involved in distinct functional processes are subject to different selective pressures. We investigated whether there is an amino acid composition bias (AACB) inherent in discrete subsets of proteins, and whether we could identify changing patterns of AACB during the life cycle of the social bacterium Myxococcus xanthus. We quantitatively characterised the cellular, soluble secreted, and outer membrane vesicle (OMV) sub-proteomes of M. xanthus, identifying 315 proteins. The AACB of the cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…xanthus OMVs has been shown to differ from that of the periplasm and outer membrane, hinting to the presence of a dedicated protein sorting mechanism to load OMVs (Kahnt et al, 2010;Evans et al, 2012;Berleman et al, 2014;Whitworth et al, 2015). OMVs contain several proteins with predicted hydrolytic functions, as well as antibiotics, such as myxovirescin A and the antifungal myxalamide (Kahnt et al, 2010;Evans et al, 2012;Berleman et al, 2014).…”
Section: The Delivery Of Predation Factorsmentioning
confidence: 99%
“…xanthus OMVs has been shown to differ from that of the periplasm and outer membrane, hinting to the presence of a dedicated protein sorting mechanism to load OMVs (Kahnt et al, 2010;Evans et al, 2012;Berleman et al, 2014;Whitworth et al, 2015). OMVs contain several proteins with predicted hydrolytic functions, as well as antibiotics, such as myxovirescin A and the antifungal myxalamide (Kahnt et al, 2010;Evans et al, 2012;Berleman et al, 2014).…”
Section: The Delivery Of Predation Factorsmentioning
confidence: 99%
“…The foraging of bees is synergistic because signaling between individuals enhances each individual's ability to locate food. Myxobacteria have an extensive repertoire of signaling proteins . They respond to molecules secreted by some prey, and motility‐based behavioral changes have been observed during predation .…”
Section: Are Any Modes Of Joint Action Manifested During Predation?mentioning
confidence: 99%
“…Myxobacteria have an extensive repertoire of signaling proteins. [14,21] They respond to molecules secreted by some prey, and motility-based behavioral changes have been observed during predation. [66,67] Nevertheless, virtually no transcriptional changes were observed in the predator when exposed to prey Escherichia coli (E. coli), [68] precluding cell-cell signaling dependent stimulation of predatory gene expression.…”
Section: Are Any Modes Of Joint Action Manifested During Predation?mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the PG-lytic enzymes, Evans et al (2012) identified PG-specific amidases and lysozyme within the OMVs released by this predator. Yet 2 separate high-throughput proteomic studies of these OMVs resulted in the identification of only a single N-acetylmuramoyl-L-alanine amidase (Kahn et al 2013;Berleman et al 2014); no autolysin was identified in a third, and most recent, study (Whitworth et al 2015). Again, it is possible that the annotations of the databases are incomplete or incorrect to preclude complete identification of the OMV proteomes.…”
Section: Autolysins and Predatory Omvsmentioning
confidence: 99%